Raffael - Blažíček, Oldřich J. 1914-1985 (Odeon, 1982)
Monografie věnovaná dílu italského renesančního malíře Raffaela /1483-1520/.
Keywords: Raffael, -- 1483-1520; malíři; malířství; osobnosti; painting; biografie